Childhood cancer incidence in Canada: demographic and geographic variation of temporal trends (1992–2010) - Lin Xie (Health Promotion and Chronic Disease Prevention in Canada, 2018)
Introduction: Surveillance of childhood cancer incidence trends can inform etiologic research, policy and programs. This study presents the first population-based report on demographic and geographic variations in incidence trends of detailed pediatric diagnostic groups in Canada. Methods: The Canadian Cancer Registry data were used to calculate annual age-standardized incidence rates (ASIRs) from 1992 to 2010 among children less than 15 years of age by sex, age and region for the 12 main diagnostic groups and selected subgroups of the International Classification of Childhood Cancer (ICCC), 3rd edition. Temporal trends were examined by annual percent changes (APCs) using Joinpoint regression. Results: The ASIRs of childhood cancer among males increased by 0.5% (95% confidence interval (CI) = 0.2–0.9) annually from 1992 to 2010, whereas incidence among females increased by 3.2% (CI = 0.4–6.2) annually since 2004 after an initial stabilization. The largest overall increase was observed in children aged 1–4 years (APC = 0.9%, CI = 0.4–1.3). By region, the overall rates increased the most in Ontario from 2006 to 2010 (APC = 5.9%, CI = 1.9–10.1), and increased non-significantly in the other regions from 1992 to 2010. Average annual ASIRs for all cancers combined from 2006 to 2010 were lower in the Prairies (149.4 per million) and higher in Ontario (170.1 per million). The ASIRs increased for leukemias, melanoma, carcinoma, thyroid cancer, ependymomas and hepatoblastoma for all ages, and neuroblastoma in 1–4 year olds. Astrocytoma decreased in 10–14 year olds (APC = −2.1%, CI = −3.7 to −0.5), and among males (APC = −2.4%, CI = −4.6 to −0.2) and females (APC = −3.7%, CI = −5.8 to −1.6) in Ontario over the study period. Conclusion: Increasing incidence trends for all cancers and selected malignancies are consistent with those reported in other developed countries, and may reflect the changes in demographics and etiological exposures, and artefacts of changes in cancer coding, diagnosis and reporting. Significant decreasing trend for astrocytoma in late childhood was observed for the first time.